Examining the Digital Entrepreneurship Education Effectiveness on Soft Skills among Undergraduates - Nur Thara Atikah Zainal; Kelvin Yong (2020)
The Fundamentals of Entrepreneurship Acculturation Course is one of the curriculum of higher learning institutions in Malaysia to enhance the soft skills of undergraduates required for the job market. The emergence of digital technologies has led to the integration of the digital entrepreneurship module into the existing entrepreneurship course. Nonetheless, there is a dearth of recent literature relevant to the effectiveness of digital entrepreneurship education and its impact on students’ soft skills. The main purpose of this study is therefore to investigate the impact of digital entrepreneurship education on soft skills of undergraduates at public higher learning institution in East Malaysia. The study collected secondary data which included course feedback forms of 2,454 second year undergraduate students from two different academic years. Overall, the findings show that the digital entrepreneurship education enhanced the students’ soft skills. However, leadership skills were the lowest that students gained in both academic years. The findings provide practical implications for higher learning institutions on the importance of digital entrepreneurship education to the soft skills of undergraduates, and on the need to improve teaching and learning methods to equally enhance the soft skills.